Investimento em saneamento no Brasil e seus efeitos sobre crescimento e desigualdades regionais - Yasmin Pitaluga Miranda (2022)
This study analyzes the possibility of sanitation be used as an instrument to growth and regional inequalities reduction by evaluating the results of different investment scenarios proposed. The analysis considers the New Sanitation Regulatory Framework, Law 14.026/20, which sets goals for universal access to drinking water and sewage collection and treatment by 2033. To emphasize the importance of sanitation, studies concerning its interconnection with health, education and income are hereby presented. Two analyzes are carried out, based on investments made between 2014 and 2033 and investments planned until 2033, using data from PAC, MDIC and BNDES as well as the amount of investment necessary to achieve universal access, according to PLANSAB. At the end of 2033, GDP growth would be 1.84% higher compared to the baseline scenario, with a small reduction in the Gini index. Regional results suggest states with greater deficits in sanitation could enjoy more positive economic results, particularly in the long term. Sectorial results, especially in the projection scenario, in the investment operation phase, show that production in sanitation sector would grow more expressively in the North and Northeast macro- regions, where the worst indicators of access to water and sanitation are.